Indikator Antropometri Dini sebagai Penanda Risiko Stunting dengan Anemia pada Balita - Arisanty Nur Setia Restuti; Adhiningsih Yulianti; Putri Rahayu Ratri (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Stunting and anemia are two chronic nutritional problems that frequently occur concurrently among young children and have long-term impacts on the quality of human resources. Anthropometric factors at birth and nutritional status during early childhood are believed to play an important role in the development of these conditions. This study aimed to analyze the correlation between birth length (BL), birth weight (BW), mid-upper arm circumference (MUAC) and head circumference (HC) with the occurrence of stunting accompanied by anemia among children under five years of age. This study employed an analytical observational design with a cross-sectional approach. The study subjects were children aged 6–59 months who experienced stunting and anemia. Data on BL and BW were obtained from the Maternal and Child Health handbook, while MUAC and HC were measured directly. Statistical analysis was performed using the Pearson correlation test. A significant correlation was found between BL and MUAC (p<0,05) with a positive strength of association (r = 0.634). BL and MUAC showed a strong and significant correlation. These findings reinforce the concept that stunting and anemia are chronic nutritional problems that originate early in life and persist into early childhood. This study concludes that BL as an anthropometric indicator is a risk marker for the occurrence of stunting accompanied by anemia among children under five, as reflected by its positive correlation with MUAC. This finding indicates that growth impairment and poor nutritional status in children with stunting and anemia begin during the prenatal period and continue into early childhood.